Determination of the alkaline phosphatase (ALP) in diabetic patients. (Eurasian Medical Research Periodical, 2022)
Diabetes is a disease known since ancient times. The Greek physician Aretaeus noticed in early 200 BC that some patients had symptoms of frequent urination and extreme thirst, and he called this phenomenon “diabetes.” In 1675 AD, the scientist Thomas Willis added the word Mellitus, which in Latin means "sweet as honey", after he noticed that the blood and urine of diabetics had a sweet taste, so the name of this disease became "Diabetes Mellitus" or diabetes. The researcher used the descriptive methodology, he got to me the most important conclusions and recommendations in the research